2018
DOI: 10.1080/02699052.2018.1432892
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of neuroinjury biomarkers after sport-related concussion: from the subacute phase to clinical recovery

Abstract: Objectives: To characterise a panel of neuroinjury-related blood biomarkers after sport-related concussion (SRC). We hypothesised significant differences in biomarker profiles between athletes with SRC and healthy controls at both subacute and medical clearance time points. Methods: Thirty-eight interuniversity athletes were recruited over two athletic seasons (n = 19 SRC; n = 19 healthy matched-control). High-sensitivity immunoassay was used to evaluate 11 blood analytes at both the subacute phase after SRC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…The summation of the results in the present study are consistent with other facets of secondary injury previously observed following SRC by our group, namely oxidative stress 56 , and inflammation 57,58 . Specifically, we have previously identified higher concentrations of the oxidative stress marker PRDX-6 in athletes following SRC 56 , and also found that days to medical clearance was positively correlated with blood concentrations of the inflammatory chemokines monocyte chemoattractant protein (MCP)-1 and MCP-4 59 .…”
Section: Discussionsupporting
confidence: 93%
“…The summation of the results in the present study are consistent with other facets of secondary injury previously observed following SRC by our group, namely oxidative stress 56 , and inflammation 57,58 . Specifically, we have previously identified higher concentrations of the oxidative stress marker PRDX-6 in athletes following SRC 56 , and also found that days to medical clearance was positively correlated with blood concentrations of the inflammatory chemokines monocyte chemoattractant protein (MCP)-1 and MCP-4 59 .…”
Section: Discussionsupporting
confidence: 93%
“…2). Lastly, our study focused on evaluating the relationship between symptom burden and systemic inflammation at a single time point post-injury, therefore follow-up studies are required to characterize this relationship throughout recovery; given our groups' prior findings of persistent symptoms at medical clearance utilizing both advanced neuroimaging [63,64] and blood biomarkers [65], it remains unclear how symptom burden tracks biological recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Our study sample was limited to male participants; future studies should also consider a sample size large enough to explore potential differences between males and females giving the growing body of literature identifying differential responses postconcussion. 22–24 Furthermore, while the clinical decision to medically clear a patient is well established (ie, the achievement of asymptomatic status following a graded exertional protocol), previous research has demonstrated a great degree of variability in individual physician practices with respect to assessment, management and clearance following concussion. 25 Also, there are some practical issues that should be acknowledged with using medical clearance as an outcome measure, such as physician availability and scheduling, patient availability, and urgency.…”
Section: Discussionmentioning
confidence: 99%